Detecting Tissue Deterioration after Brain Injury: Regional Blood Flow Level versus Capacity to Raise Blood Flow. Issue 7 (July 2014) - Feuerstein, Delphine; Takagaki, Masatoshi; Gramer, Markus; Manning, Andrew; Endepols, Heike; Vollmar, Stefan; Yoshimine, Toshiki; Strong, Antony J; Graf, Rudolf; Backes, Heiko
Regional cerebral blood flow ( rCBF ) is spatially and temporally adjusted to local energy needs. This coupling involves dilation of vessels both at the site of metabolite exchange and upstream of the activated region. Deficits in upstream blood supply limit the 'capacity to raise rCBF ' in response to functional activation and therefore compromise brain function. We here demonstrate in rats that the 'capacity to raise rCBF ' can be determined from real-time measurements of rCBF using laser speckle imaging during an energy challenge induced by cortical spreading depolarizations (CSDs). Cortical spreading depolarizations (CSDs) occur with high incidence in stroke and various other brain injuries and cause large metabolic changes. Various conditions of cerebral perfusion were induced, either by modifying microvascular tone, or by altering upstream blood supply independently. The increase in rCBF per unit of time in response to CSD was linearly correlated to the upstream blood supply. In an experimental model of stroke, we found that this marker of the capacity to raise rCBF which, in pathologic tissue may be additionally limited by impaired vasoactive signaling, was a better indicator of the functional status of cerebral tissue than local rCBF levels.